Analisis Miskonsepsi Peserta Didik SMP Pada Materi Getaran dan Gelombang - Aodina, Eliza; Kaulfa, Laely; Busyairi, Ahmad (Jurnal Penelitian dan Pembelajaran Fisika Indonesia, 2024)
One of the physics materials that students often experience misconceptions is vibration and wave material. Students who often experience misconceptions in vibration and wave material have several factors including abstract material concepts, from everyday experiences, difficulties in connecting the concepts of vibration and wave material, and learning method models. This study aims to identify forms of misconceptions that commonly occur in grade VIII students related to the concept of vibration and waves. Through a literature review, it was found that misconceptions that often arise include misunderstandings about the relationship between period and frequency, wave properties, and the differences between transverse and longitudinal waves. Using interactive and varied learning media can also increase student learning motivation and reduce misconceptions. The three-tier diagnostic test is an effective instrument for revealing student misconceptions in depth. The results of this literature review are expected to be the basis for the development of more effective diagnostic instruments and learning strategies to overcome misconceptions in vibration and wave metrics. Keywords: Misconceptions, Vibrations and Waves.